ANCAMAN DEEPFAKE DAN DISINFORMASI BERBASIS AI: IMPLIKASI TERHADAP KEAMANAN SIBER DAN STABILITAS NASIONAL INDONESIA - Nurdin, Sri Wahyuni; Nugraha, Imam Fadhil (JIMR : Journal Of International Multidisciplinary Research, 2025)
The development of artificial intelligence (AI), particularly deepfake technology, has posed a serious threat to Indonesia’s national security. Deepfakes enable the creation of highly realistic yet fabricated audio-visual content, which can disseminate disinformation, manipulate public opinion, and generate systemic uncertainty within society. In the context of Indonesia, with high internet penetration but low levels of digital literacy, this phenomenon amplifies the risks to institutional legitimacy, democratic processes, and social cohesion. This study employs a qualitative descriptive-narrative approach through literature review and thematic analysis to examine the dynamics of this threat. The findings indicate that AI-based disinforma tion is not merely a technical issue, but also a psychological, political, and structural one. Addressing this challenge requires regulatory reform, strengthened digital forensic capabilities, and broad-based digital literacy improvement. Without a comprehensive and adaptive response, deepfake disinformation may evolve into an effective tool of destabilization in the era of modern information warfare.